Interim measures in support of arbitration in Ukraine: lessons from JKX Oil & Gas et al v Ukraine and the recent reform of Ukrainian legislation. (4th June 2018) - Hamama, Olga; Sendetska, Olga
Abstract: On 9 June 2015, the Kyiv Pechersk District Court in Ukraine enforced an award rendered by an emergency arbitrator under the Arbitration Institute of the Stockholm Chamber of Commerce (SCC) Arbitration Rules in the investment arbitration case JKX Oil & Gas et al v Ukraine . The judgment resulted from the first ever attempt to enforce an emergency arbitrator award in Ukraine. It was also reported as the first successful enforcement of an emergency arbitrator award against a state. The outcome is of particular importance in Ukraine, where courts were previously reluctant to order interim measures in support of arbitration. The enforcement proceedings for the JKX Oil & Gas et al v Ukraine emergency arbitrator award also demonstrate why a reform of Ukrainian arbitration-related law was necessary. On 15 December 2017, amendments to the Ukrainian Code of Civil Procedure entered into force regulating, inter alia, interim measures in support of arbitration. This article will analyse whether these changes may aid efficient enforcement of interim measures in Ukraine in the future and whether an emergency arbitrator award remains a viable option in arbitration proceedings related to Ukraine.